Comparison the effectiveness of computerized cognitive behavioral therapy versus clinical intervention in social phobia disorder - hoseyn ghamari givi; abdolsamad aagh (Faṣlnāmah-i Farhang Mushavirah va Ravān/Darmānī, 2010)
Social phobia disorder is characterized by a marked and persistent fear of social or performance situations and maybe associated with embarrassment or humiliation. This research was aimed to exploring the effectiveness of cognitive behavioral therapy in three methods of web-based intervention, software package and clinical intervention in comparison with control group for social phobia disorder. The sample of study was consisted of 68 students whith social phobia disorder who were selected using available sampling from among patients who were seeking treatment at Online and Presence Consultation Center of University of Mohaghegh Ardabili, and then assigned in three experimental groups and one control group. In this research Social Phobia Inventory and Structured Clinical Interview for DSM Disorders were used. The results showed that there was significant difference between cognitive behavioral therapy (web- based and software package) in comparison with control group in reducing scores of social phobia inventory but there was no significant difference between the two methods in terms of their effectiveness. Furthermore, there was significant difference between two mentioned methods and clinical intervention, in a way that clinical intervention was more effective than the other methods. Results indicate that computerized cognitive behavioral therapy is a feasible and acceptable method in treatment of social phobia disorder.